Finite element analysis of square CFST beam strengthened by CFRP composite material. (November 2015) - Al Zand, Ahmed W.; Badaruzzaman, Wan Hamidon W.; Mutalib, Azrul A.; Qahtan, A.H.
Abstract: Concrete-filled steel tubes (CFSTs) have become the most recommended composite structural members in many modern structures. These members may need upgrading or strengthening like any conventional structural members for many reasons. In this research, Finite element (FE) models are prepared to investigate the behavior of square CFST beams, partially strengthened with carbon fiber-reinforced polymer (CFRP) sheets. The proposed FE models are verified with existing experimental test results. Several parameters are studied in this research, including various CFRP wrapping lengths/layers, steel tube yielding strengths, depth-to-thickness ( D / t ), and length-to-depth ( L / D ) ratios. The application of CFRP to strengthen the CFST models found less improvement in the elastic range compared with the significant improvement in the plastic range. The CFRP is found to be not very effective if applied along 50% of models length compared with those applied along 75% or more of their length because of the delamination failure. Load improvement ratios achieved close values when strengthening the models along 75% and 100% of their length with CFRP sheets up to three layers. Better load improvement ratios were observed for the strengthened models with higher L / D and D / t ratios and for the models with lower steel yield strength when adopting the same strengthening scenario. Highlights: Establishing the optimum strengthen behavior of CFST beams by flat CFRP sheets. Multiple layers of flat CFRP sheets increase the beam's capacity up to certain limit. Delamination failure occurred with increasing CFRP layers when applied partially. Beams with higher D / t and L / D ratios showed better loads improvement. The behavior of adhesive material implemented accurately in the FE analysis.